(untitled) (Sains Humanika, 2017)
The issue of industry involvement in skills training programs since the 1950s has shown the level of industry involvement is still low in Malaysia. The government’s efforts to involve high finance allocation in encouraging industry involvement also did not show good results. In 9th Malaysia Plan (2005-2010), the Economic Planning Unit (EPU) is targeting 6,300 industries to engage in National Dual Training System (NDTS) program. However, data from NDTS Q-Fact showed that until the end of the 2010, only 1,028 industries involved. In fact, until the end of the 10th Malaysia Plan in 2015, only 3,775 industries involved. This article proposed the framework for industry involvement collaboration of the NDTS programme in Malaysia. The method used in this article is a systematic review that takes previous studies on industry involvement in skills training collaboration into consideration. The framework built based on the organisation factors that influence the involvement of industry that described in these three variables: organisational governance, organisational motivation, organisational behaviour. Construct for each variable will be explained to see its relations with industrial involvement in the aspect of collaboration. Key findings from this study will form a strategic indicator of industrial involvement in implementation of NDTS programme in Malaysia.